An unusual aggressive presentation of late onset sepsis due to Staphylococcus aureus MRSA producing Panton-Valentine Leukocidin in preterm neonate: An unusual case of severe sepsis in preterm neonate - Capasso, Letizia; Cerullo, Julia; Lo Vecchio, Andrea; Coppola, Clara; Lepore, Lorenza; Marra, Valentina; Antonaki, Eleni; Raimondi, Francesco (Acta Biomedica Atenei Parmensis, 2021)
We report an unusual and rare case of infection from methicillin resistant Staphylococcus aureus (MRSA) producing Panton-Valentine leukocidin in a preterm neonate in NICU. On day of life 8, a preterm baby boy suddenly developed arthritis, giant cutaneous abscesses and an osteomyelitic focus with pour clinical condition. This very aggressive presentation of infection from MRSA push us to test Panton-Valentine leukocidin resulted positive and to test contacts to discover the bearer of the germ. MRSA producing Panton-Valentine leukocidin is an unusual case of infection in preterm neonate that has not been reported elsewhere. A very aggressive sepsis in neonates from Staphilococcus aureus should evoke the need to test Panton-Valentine leukocidin to rapidly establish an appropriate treatment. We underline also the importance to test contacts to establish promptly a decontaminant therapy